THE IMPACT OF MANIPURI DANCE IN THE ROYAL COURT OF TRIPURA - Singha, Sudeshna (International Journal of Research -GRANTHAALAYAH, 2021)
Manipuri people are a small group of Tripura. During the time of the Maharaja’s these people’s song and music attained a very special status. Firstly, it was royal palace centered, secondly, in various places of Tripura in the Manipuri dominant areas and in their temples, mandaps or at various festivals. According to many writers it can be said clearly like a mirror the Manipuri culture touched Tripura during the tenure of Rajdhar Manikya from 1785 – 1804. And at that very same time the tenure of Manipuri king Bhagyachandra is 1759 – 61 and 1763 – 1798. The Manipuri Raas established by him later on achieved the status of Indian classical dance. In later times, Manipuri culture started influencing the royal palace right after Harisheshwari became the queen of Tripura. In that time’s Agartala that means in Old Agartala, near to the royal palace for the first time Radhamadhab temple was established. The name of the Manipuri dominant areas in this Old Agartala is Nalgaria. This is where Maharani Tulsibati took birth. According to the writer Udainarayan Adhikari – “The Manipuri’s who came to Tripura with Princes Harisheshwari of Manipur at the fag end of the 18th century as a result of her wedding with Rajdhar Manikya II of Tripura, were settled in a village near capital old Agartala. This village now goes by the name of Mekhlipara, because Mekhli was the Tripura name for Manipur in the days of yore. There is a small township called Ranir Bazar a few kilometres east of Old Agartala or Khayerpur. It was founded by the Manipuri queen Maharani Tulsibati. Her parents lived at Nalgadiya a little east of Ranirbazar. So she founded this bazaar or township in order to develop this area. The name Ranirbaazar reminds us that it was founded by a Rani (Maharani Tulsibati).